Memperkuat Rasa Nasionalisme dan Penerapan Nilai-Nilai Pancasila dalam Kehidupan Sehari-Hari Sisw/Siswi SDN 1501 Desa Hurung Jilok - Holongniroha Lubis; Nur Hakima Akhirani Nasution (Sekolah Tinggi Agama Islam Barumun Raya (STAI BR) Sibuhuan, 2023)
It is hoped that this service can increase Pancasila values in everyday life, and further increase the sense of nationalism among people in Pasir Hurung Jilok Village, Padanglawas Regency. The methods used in carrying out activities are educational methods and explanations in the form of videos and materials for SD 1501 students to familiarize and apply Pancasila values in everyday life. The activity ran smoothly with an enthusiastic welcome from teachers, children and the community who took part in activities with a sense of nationalism and the application of Pancasila values. There is support from the school and the local community in activities to strengthen a sense of nationalism and the application of Pancasila values.